ROLE OF PADA ABHYANGA AS PREVENTIVE ASPECT W.S.R TO EYE DISORDERS: A CONCEPTUAL STUDY - Rashmi, *K; Deshpande, Swati S. (International Journal of Ayurveda and Pharma Research, 2015)
Ayurveda aimed in prevention and cure of physical and mental health. In Ayurveda, Dinacharya is one of the concept which helps to fulfill this aim of Ayurveda. Vitality enhancing technique which is incorporated in massage of the feet is called Padabhyanga. It is one of the prophylactic principles mentioned in Ayurvedic dinacharya. The hectic computerised life style, faulty food habits, stress and strain, irregular sleeping habits and negligence in following daily and seasonal regimen provoke many eye problems. By doing Padaabhyanga, Kharatwa, Stabdata, Rukshata, Shrama, Suptata of pada relieved and Bala, Sthairya improved, Drustiprasaadakara. It also prevents Grudrasi vaata, Pada sputana, Sirasnaayu sankocha.In the centre of the feet 2 Siras are situated which are directly connected to the eyes, these transmit the effect of the medicines applied over the feet in the form of massage. Hence every person should need make use of Padabhyanga. Major cause of blindness for prevalence are cataract, glaucoma, diabetic retinopathy, Age related macular degeneration, refractive errors. There by Paada Abhyanga through its Vaata-ameliorating action is responsible for better function of Chakshurindriya. According to Sushrutacharya, by practice of Snehana karma, which results in Utpatti of Pratyagradhatu – Navadhatu. such that degenerative changes related to eye are antagonized by the Snehana karma. Padaabhyanga is helpful in preventing above said diseases which causes the blindness. Hence this conceptual study is made to explain the mode of action and effect of Pada Abhyanga to increase and maintain the visual acuity.